MOLECULAR MECHANICS OF WATER AND ITS ROLE IN INCREASE OF VIABILITY OF BIOSYSTEMS (STATE-OF-THE-ART REVIEW) - E. Sh. Ismailov; M. K. Kazimagomedov; G. M. Abacarov (Вестник Дагестанского государственного технического университета: Технические науки)
In work modern data on molecular structure of water in the form of the state-of-the-art review are considered. The irreplaceable role of water in activity processes is shown. Ways of effective use of active forms of water in technologies are defined.